Effects of scalable, wordless, short, animated storytelling videos on hope in China: a nationwide, single-blind, parallel-group, randomised controlled trial - Chen, Wenjing; Adam, Maya; Geldsetzer, Pascal; Jiao, Lirui; Gates, Jennifer; Zhao, Jinghan; Bärnighausen, Till; Chen, Simiao; Wang, Chen (Journal of global health, 2025)
Background People with higher levels of hope are more likely to be vaccinated. Short, animated story (SAS) videos have shown promise for communicating health messages and boosting hope in certain populations. We explored the potential of scalable SAS vaccine promotion videos for boosting hope levels among Chinese adults. - Methods In this single-blind, parallel-group, randomised controlled trial, we recruited adults from China through quota sampling. Participants were randomly assigned in a 1:1:1:1 ratio to one of three SAS video intervention groups (humour, analogy, or emotion) or a control group. After watching the videos or being assigned to the control group, participants completed the Adult Hope Scale. Level of hope among participants was compared between each intervention group and the control group, as well as among the different intervention groups, with P-values adjusted for multiple comparisons. - Results We included 12 000 participants aged 18 and above, residing in China, in our analysis. In the main analysis and sensitivity analyses, no significant intervention effects were observed in any of the three intervention groups. Furthermore, comparisons among the intervention groups showed no significant differences, indicating no variation in the effects of the three intervention videos. In subgroup analyses, however, we observed significant differences among regional subgroups (P < 0.05), with Video A (humour) boosting hope in participants from the southern and southwestern regions, when compared with other regions. - Conclusions While the short, single-exposure SAS videos did not significantly enhance overall hope levels among Chinese adults, the effectiveness of humour in certain sub groups highlights the cultural adaptability of health communication strategies. Given its scalability and accessibility, this approach warrants further research to refine narrative techniques, optimise engagement across diverse populations, and explore its broader application in global health communication.